Discurso e representação sobre as espartanas no período clássico - Lessa, Fábio de Souza (Synthesis.)
Spartan society has acquired prominence in historiographical analyses produced since the eighteenth century onwards. Among the various elements which composed this society the figure of the Spartan woman was undoubtedly a widely debated aspect. Spartan women were considered from two distinct perspectives: at times represented in the discourse of classical authors as a model of social conduct; on other occasions seen as having excessive 'freedom' and inordinate sexual practices. We aim to compare the images constructed by Xenophon and Aristotle to verify the relations between the respective discourses and the social context in the classical period (the fifth and fourth centuries BC)